Stakeholder Perspectives on Optimizing Communication in a School‐Centered Asthma Program. (2nd November 2017) - Snieder, Hylke M.; Nickels, Sarah; Gleason, Melanie; McFarlane, Arthur; Szefler, Stanley J.; Allison, Mandy A.
ABSTRACT: BACKGROUND: School‐centered asthma programs (SAPs) can be an effective intervention to improve asthma control for underserved populations but little is known about how key stakeholders communicate within these programs. Therefore, our aim was to identify key components of effective communication in a SAP. METHODS: Primary care providers (PCPs), parents and school nurses associated with a SAP in Denver, Colorado participated in interviews and focus groups about their views on effective communication. Interview and focus group guides were developed using an appreciative inquiry approach and transcripts were analyzed via an iterative coding approach. RESULTS: We conducted 3 focus groups with school nurses (N = 13), interviews with parents (N = 12) and PCPs (N = 10). Stakeholders identified multiple themes that enable communication, namely personal relationships, clear roles, integration of technology, adequate resources, and accessibility. CONCLUSIONS: Communication in SAPs is most effective when there are clearly delineated roles with the school being the focal point for education and monitoring of asthmatic students and PCPs being the focal point for diagnosis and changes in care. Communication should take place using modern technology that is integrated into existing workflow. Information sharing is most likely to be successful if there is deliberate relationship building.